Efficacy and Toxicity of Three Induction Chemotherapy Regimens in Locoregionally Advanced Nasopharyngeal Carcinoma: Outcomes of 10-Year Follow-Up - Peng, Hao; Chen, Binbin; He, Shuiqing; Tian, Li; Huang, Ying (Frontiers in Oncology, 2021)
Background/Objective: We aimed to compare the 10-year survival outcomes of induction docetaxel plus cisplatin and 5-fluorouracil (TPF), docetaxel plus cisplatin (TP) and cisplatin plus 5-fluorouracil (PF) regimens additional to concurrent chemoradiotherapy (CRT) in locoregionally advanced nasopharyngeal carcinoma (NPC). Methods: Eligible patients with newly diagnosed stage III-IVA NPC were included. Propensity score matching (PSM) was used to balance prognostic covariates. Survival outcomes and toxicities between different groups were compared. Results: A total of 855 patients between 2009 and 2012 were included, with 395 (46.2%), 258 (30.2%) and 202 (23.6%) receiving TPF plus CRT, TP plus CRT and PF plus CRT regimens, respectively. After a median follow-up of 111.8 months, multivariate analysis both in the whole cohort and PSM selected 202 pairs showed that TPF plus CRT and TP plus CRT achieved significantly better 10-year overall survival (OS) than PF plus CRT. Sensitivity analysis after excluding patients with T3-4N0 disease demonstrated that TPF plus CRT still achieved significantly better OS than PF plus CRT (HR, 0.580; 95% CI, 0.395-0.852; P = 0.005) while the difference between TP plus CRT and PF plus CRT was marginally significant (HR, 0.712; 95% CI, 0.503-1.008; P = 0.056). With regard to toxicity profile, PF regimen achieved the lowest grade 3-5 toxicities (27.3%). Conclusion: TPF plus CRT and TP plus CRT were better than PF plus CRT in improving the 10-year OS of patients with stage III-IVA NPC.